Undetermined cause of mortality in horses in Argentina - Olguin Perglione, Cecilia; Vissani, Maria Aldana; Ivanissevich, A.; Minatel, L.; Canteros, Cristina; McAulife, S.; Kennedy, Laura; Barrandeguy, Maria Edith; Camio, Guadalupe (2017)
The aim of this report is to describe the features and clinical findings in a series of equine mortalities occurred in a Thoroughbred and Quarter Mile horse breeding farm located in Canuelas, Buenos Aires Province, Argentina. The affected population consisted of 20 nursing foals (between 3 to 6 months of age). They were allowed to graze freely on natural pasture, without supplementation of dry (hay) or other commercial equine feed.